Spatial Distribution Characteristic of Antimony in Typical Paddy Soil of Eastern Hunan Province, China - Wang, ChenRan; Wan, DaJuan; Cao, XueYing; Wang, Huan; Chen, JiaQi; Ouyang, NingXiang; Zhang, YangZhu; Tan, ChangYin (Frontiers in Environmental Science, 2021)
Taking the eastern part of Hunan province as the research area, 34 sampling sites were set up and 198 samples were collected from representative paddy soil, the distribution characteristics of antimony were studied. The results showed that: (1)The Sb content of paddy soil surface layer fell in a region of 0.07-11.00 mg/kg with geometric mean of 1.56 mg/kg. (2)The spatial distribution of Sb content in paddy soil of various areas followed an order of Yueyang City> Changsha City> Zhuzhou Sity> Xiangtan City (3)The Sb showed a strong migration in paddy soil of research area, and its content was mainly increased firstly and then decreased, or gradually decreased with increasing profile depth. (4)Soil parent material had an obvious effect on the Sb content of substratum.